Flux determination for the 18 MeV Neutron Beam at NCSR “DEMOKRITOS’’ using the multiple foil activation method - Amanatidis, Lamprianos; Chasapoglou, Sotiris; Vlastou, Roza; Diakaki, Maria; Kokkoris, Michael; Michalopoulou, Veatriki; Bari, Zoe; Axiotis, Michael; Lagoyannis, Anastasios (HNPS Advances in Nuclear Physics, 2024)
Following the upgrade of the tandem accelerator at NCSR “Demokritos”, the determination of the new neutron flux was necessary for further neutron induced experiments. For the investigation of the energy dependence of the neutron flux at 18 MeV, the multiple foil activation technique has been used, in combination with two codes. With Monte Carlo simulation based code MCNP5 and unfolding code SAND-II .